Mental Health Problems among Elementary School Students Mandated to e-Learning: A COVID-19 Rapid Review Caveat - Renée M. D'Amore; Angelina N. Halpern; Lauren R. Reed; Kevin M. Gorey (International Journal of School Social Work, 2023)
Extended lockdowns during the COVID-19 pandemic mandated millions of students worldwide to e-learning and by default made many of their parents proxy homeschool teachers. Preliminary anecdotal, journalistic and qualitative evidence suggested that elementary school children and their parents were probably most vulnerable to this stressor and most likely to experience mental health problems because of it. We responded with a rapid review of 15 online surveys to estimate the magnitude of such risks and their predictors between 2020 and 2021. The pooled relative risk of mental health problems among school children and their parents was substantial (RR = 1.97). Moreover, this synthetic finding did not differ significantly between 10 child mental health outcomes (primarily measures of anxiety or depression) and five parental stress outcomes. Such risks to children and parents were incrementally greater among Latinx (RR = 1.81) and Black families (RR = 2.50) than among non-Hispanic White families (RR = 1.58) in the USA. Finally, such risks in the West (RR = 2.12) were observed to be greater than those in the East (RR = 1.36). Grave risks were experienced worldwide, but the pandemic once again clarified for the world that such structural violence, in this instance, in elementary school systems, was much more prevalent and virulent among Black and Brown families in places like the USA. Educational practice implications, future research and pandemic preparedness needs are discussed.
Keywords: Anxiety; Coronavirus Pandemic; COVID-19; Elementary School; e-Learning; Homeschooling; Mental Health; Online Learning; Parental Stress; School Children